Analysis of the effect of the number of blades on the palm frond counter tool on the counting results - Fajar David Aminuddin; Anis Siti Nurrohkayati; Agus Mujianto; Hery Tri Waloyo (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
The growth of oil palm plantations in Indonesia, especially in Kalimantan and Sumatra, has resulted in an increase in palm oil waste from harvesting and tree care, both in the form of liquid waste and solid waste. As waste, palm fronds and leaves experience natural decomposition for about 4 months, which can cause a very large buildup and become a nest for pests to inhabit before decomposing. Designing an oil palm frond and leaf shredding machine involves designing special blades mounted on a rotating shaft, as well as a strong support structure to handle tough fiber materials, such as oil palm fronds and leaves, by producing flakes that can be used as organic fertilizer or ingredients. animal feed. The aim of this research is to create and test testing machines for chopping palm fronds and leaves showing that different blades have the ability to chop quite fine parts of the leaves with a chop length of between 20 mm and 50 mm, and the hardest part, palm fronds, can also be chopped finely. The amount of time spent is 1 minute and is able to chop 3 palm fronds. In 5 repetitions, an average time of 1 minute was obtained to chop the fronds. Based on the effective capacity of 5 repetitions on 19 blades, the average result was 1.45 kg/minute. Meanwhile, for effective capacity from 5 repetitions on 24 blades, the average result was 1.57 kg/minute and for effective capacity from 5 repetitions on 26 blades, the average result was 1.76 kg/minute